The extent to which circular economy principles have been applied in the design of medical devices for low-resource settings in Sub-Saharan Africa. A systematic review - Samenjo, Karlheinz Tondo; Oosting, Roos Marieke; Bakker, Conny; Diehl, Jan Carel (Frontiers in Sustainability, 2023)
Healthcare facilities in low-resource settings in Sub-Saharan Africa are plagued with issues of non-functional and obsolete medical devices, which ultimately end up prematurely disposed of as waste. With increasing healthcare demands, stopping medical device disposal is imperative. One way to achieve this is to leverage circular economy principles in designing medical devices. Circular economy principles aim to retain products and their constituent to be reused over time in the economic system. However, to what extent this has been applied in designing medical devices specifically for low-resource settings in Sub-Saharan Africa is missing in literature. Based on a systematic review of 29 out of 1799 screened scientific papers, we identified the use of circular economy principles of durability, maintenance, repair, and upgrade in designing medical devices for this setting. Whether these principles were intentionally applied from a circular economy approach could not be inferred in this study. The motivational basis for using these principles was to ensure medical device longevity to providing healthcare. No attention was given to the circular economy principles of refurbishment, remanufacturing, and recycling, ensuring that device components and constituent materials are recovered. These study findings serve as a launchpad for exploring how circular principles can be used to support the design of medical devices for low-resource settings in Sub-Saharan Africa. Academicians and designers of medical devices can leverage this research to contribute toward developing medical devices that support access to healthcare for people in low-resource settings and preserve earth's finite resources.